Effects of selenium source on performance, selenium retention and physiological variables in broilers - Arnaut, Pedro Righetti (2020)
Given its participation in physiological processes such as antioxidant defense systems and thyroid hormone secretion, selenium (Se) has received attention in poultry nutrition and supplementation of organic trace mineral in practical broiler feeds has been defended due to its bioavailability, which is beneficial on environmental grounds, as well because the results on response variables of interest in animal production. A dose-response assay was conducted to evaluate the growth performance, tissue mineralization, retention, and physiological responses of growing broilers fed diets containing different levels and sources of selenium. A total of 500 10-d-old male Cobb 500 broiler chicks were randomly assigned to 10 treatments with 10 replicates and five birds per replicate. Treatments were obtained from a 2×5 factorial arrangement where 2 sources of Se (sodium selenite [SS] and selenium yeast [SY]) were supplemented in semi-purified diets at 0, 0.08, 0.16, 0.24 and 0.32 mg Se/kg feed. Chicks fed SY diets had body weight (BW), and average daily gain (ADG) optimized at 0.133 and 0.130 mg Se/kg, respectively. Both Se sources linearly increased (P<0.05) the glutathione peroxidase (GSH-Px) activity in chick blood but higher values were observed in SS fed chicks (P<0.05). Both Se sources influenced the thyroid hormones serum concentration (P<0.05). Chicks fed SY exhibited greater retention of Se in the feathers (P<0.05). Organic Se as SY showed to be more bioavailable than SS. SY supplementation resulted in lower liver Se concentration as Se supplementation increased (P<0.05). Based on performance traits, the supplemental level of organic Se as SY to support the proper growth of broiler chicks is 0.133 mg Se/kg. Keywords: Glutathione peroxidase. Organic trace minerals. Selenium balance. Selenium yeast. Tissue mineralization.